HUBUNGAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) IBU DENGAN KEJADIAN DIARE PADA ANAK USIA 6-8 TAHUN DI KAMPUNG KIARA RT 03 RW 04 BALARAJA TANGERANG - Putri Izza Alzamy; Ida Faridah; Lastri Mei Winarni (Nusantara Hasana Journal, 2022)
Clean and Healthy Living Behavior (PHBS) is an effort to provide a learning experience to apply clean and healthy living behavior in everyday life. Based on the results of a preliminary study on April 20, 2022 through temporary interviews with women in Kampung Kiara RT 03 RW 04, 10 mothers were met, 6 of whom had done PHBS well, while 4 other mothers said that they still had not done PHBS properly like washing clothes still using river water. The aim of the researcher was to find out whether there is a relationship between PHBS and the incidence of diarrhea in children aged 6-8 years. This research method is quantitative with a cross sectional approach. The population in this study were 129 people who were in Kampung Kiara RT 03 RW 04. The sampling technique used was Accidental Sampling. Data analysis using Chi Square with a significant level of 0.005. The category PHBS good there were 53 people (54.1%) and the category of the incidence of diarrhea who did not experience diarrhea (74.5%). There is a significant relationship between PHBS and the incidence of diarrhea (p value = 0.001).